The potential influence of melatonin on mitochondrial quality control: a review - Lei, Xudan; Xu, Zhenni; Huang, Lingxiao; Huang, Yujun; Tu, Siyu; Xu, Lu; Liu, Dengqun (Frontiers in Pharmacology, 2024)
Mitochondria are critical for cellular energetic metabolism, intracellular signaling orchestration and programmed death regulation. Therefore, mitochondrial dysfunction is associated with various pathogeneses. The maintenance of mitochondrial homeostasis and functional recovery after injury are coordinated by mitochondrial biogenesis, dynamics and autophagy, which are collectively referred to as mitochondrial quality control. There is increasing evidence that mitochondria are important targets for melatonin to exert protective effects under pathological conditions. Melatonin, an evolutionarily conserved tryptophan metabolite, can be synthesized, transported and metabolized in mitochondria. In this review, we summarize the important role of melatonin in the damaged mitochondria elimination and mitochondrial energy supply recovery by regulating mitochondrial quality control, which may provide new strategies for clinical treatment of mitochondria-related diseases.